Developing of Thesaurus Software to Increase the Writing Quality of the Thesis of the Students at the German Language Department - Hafniati; Risnovita Sari; Suci Pujiastuti (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The use of academic vocabulary is very important to increase the writing skills and quality of the academic writing of the students. Therefore, Thesaurus software needs to be developed that contains about the academic vocabulary that help the student’s writing and increase the quality of their academic writing, and to reduce the plagiarism. The purposes of the research are; (1) to develop of German language vocabulary with a Thesaurus software that increase the quality of academic writing in German (2) to see the effectiveness of German language vocabulary with a Thesaurus software in increasing the quality of academic writing. The special purpose of the research is increasing the quality of student’s academic writing from German Language Department at the Universitas Negeri Medan with the use of Thesaurus software for German language vocabulary. The method used is the ADDIE Model with five phases: Analysis, Design, Development, Implementation and Evaluation. The data is taken from the academic writing of the students of German Language Department and the books that used in the Wissenschaftliches Schreiben’s (Academic Writing) course and then developed into the German Language academic vocabulary Thesaurus software.